Varietal variations in fruit quality parameters in strawberry (Fragaria×ananassa) harvested at different stages of color development - Kaur, A.; Sharma, A.; Singh, N.; Sharma, S. (International Journal of Horticultural Science, 2026)
Present investigation reports the fruit quality of five strawberry cultivars (‘Rania’, ‘Winter Dawn’, ‘Winter Star’, ‘Camarose’ and ‘Navelia’) harvested at different stages of color development. These cultivars showed significant variations in their chemical composition. The highest and significant values of fruit weight, hue angle and total sugars were recorded in ‘Winter Star’ cultivar at full red stage. Total phenolics and ascorbic acid content were higher in ‘Camarose’ as compared to other cultivars. These parameters and reducing sugar content in strawberry fruits showed a direct relationship with DPPH radical scavenging activity. ‘Winter Star’ exhibited highest anthocyanin content form 25% red to full ripe red stage of fruit color development with most intensive color. Total soluble sugars, reducing sugars, pH, °Brix values increased from green to full red stage whereas titratable acidity showed the reverse trend. These cultivars showed significant differences in their physicochemical and biochemical composition at different stages of ripening in agroclimatic conditions of Punjab area of northwest India.